A comparison of thermal characteristics of the small joints of the hands between patients with rheumatoid arthritis and healthy controls - Sevcan Uğur,; Yakup İrim,; Ayşe Ayça Yücel,; Hamza Feza Carlak,; Cahit Kaçar, (Archives of Rheumatology, 2024)
Objectives: This study aims to investigate the thermal characteristics of the small joints of the hands between patients with rheumatoid arthritis (RA) and healthy controls. Patients and methods: Between December 2020 and May 2021, a total of 52 RA patients (9 males, 43 females; mean age: 52.1±11.1 years; range, 38 to 68 years) who met the revised American College of Rheumatology and European League Against Rheumatism (ACR/EULAR) classification criteria and 26 healthy controls (10 males, 16 females; mean age: 51.2±8.2 years; range, 38 to 68 years) were included. Joint tenderness was evaluated using Ritchie articular index (RAI). Joint tenderness was scored from 0 to 3. Thermal data were collected from the hand regions of individuals. A FLIR T450sc microbolometer infrared thermal camera with 320×240 resolution was used for the thermography of individuals. Bilaterally proximal interphalangeal joints (1-5) and metacarpophalangeal joints (1-5) were evaluated. The mean temperature was compared between the patients and healthy controls. Results: The mean disease duration of patients with RA was 10.4±8.9 years. The mean temperature values of the joints in the patients with a RA RAI score of 0, 1, 2, 3 were 32.43±1.59°C; 32.71±1.36°C; 33.12±1.23°C; 33.60±0.99°C, respectively. The mean temperature was 31.14±1.51°C in healthy controls. The mean temperature values of the joints in the RA patients with RAI score of 0 was higher compared to healthy controls (p<0.05). Patients with a Ritchie sensitivity score of 1 had a higher mean temperature compared to patients with score of 0 (p<0.05). In RA patients, the joints with a RAI score of 1 had higher mean temperature values than the joints with RAI score of 0 (p<0.05). The mean temperature values of the joints with RAI score of 2 were also higher than the joints with RAI score of 1 (p<0.05). Conclusion: Our study results suggest that thermal imaging may be an objective tool for diagnosis and assessing disease activity in RA.